Transgressing the Canon. Emergence of the Maya Literary Movement in the Literary Critics - Alejos García, José (Estudios de Cultura Maya, 2023)
The emergence of Maya writers bursts with original, novel, and transgressing proposals, within the contemporary political context of recognition of cultural rights and vindications from First Nations peoples. Such emergence has awakened a growing interest among diverse publics. Among them, literary critics stand at a special place, as many of them have tried to define such emergence and locate it as a particular category within the national or regional literary sphere. Contrary to that assimilationistic approach, this paper argues that through their literary works Maya writers are involved in a larger artistic indigenous movement that pursues not a place in the national literature, but that aims to question and redefine the hegemonic literary canon itself. La emergencia de escritores mayas, que irrumpen con una literatura original, novedosa y de un espíritu transgresor, ocurre en el actual contexto político mundial del reconocimiento de derechos culturales y de reivindicaciones de los pueblos originarios. Este movimiento ha despertado un creciente interés entre diversos públicos, entre ellos los críticos literarios ocupan un lugar especial, analistas que en buena medida han buscado dar cuenta de esa emergencia y ubicarla como una categoría particular al interior de la esfera literaria nacional o regional. El planteamiento de este artículo es que, a contracorriente de la visión asimilacionista presente entre aquellos especialistas, mediante su producción literaria los escritores mayas participan de un movimiento artístico indígena más amplio, orientado no a encontrar un lugar en la literatura nacional, sino a cuestionar el canon literario hegemónico, a redefinir el canon mismo.